2017
DOI: 10.1088/1361-6528/aa6792
|View full text |Cite
|
Sign up to set email alerts
|

Waves in hyperbolic and double negative metamaterials including rogues and solitons

Abstract: The topics here deal with some current progress in electromagnetic wave propagation in a family of substances known as metamaterials. To begin with, it is discussed how a pulse can develop a leading edge that steepens and it is emphasised that such self-steepening is an important inclusion within a metamaterial environment together with Raman scattering and third-order dispersion whenever very short pulses are being investigated. It is emphasised that the self-steepening parameter is highly metamaterial-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 124 publications
1
19
0
4
Order By: Relevance
“…They can be stimulated in straightforward manner by opening up the NLSE using a constant background perturbed by a tiny periodic disturbance. This evolves to what is widely known as a Peregrine soliton 6 . The latter is named after Howell Peregrine, who, back in 1983, at the University of Bristol, looked brilliantly at these waves and found that they appear to come out of nowhere and then disappear quite suddenly again.…”
Section: L=ngdmentioning
confidence: 98%
See 2 more Smart Citations
“…They can be stimulated in straightforward manner by opening up the NLSE using a constant background perturbed by a tiny periodic disturbance. This evolves to what is widely known as a Peregrine soliton 6 . The latter is named after Howell Peregrine, who, back in 1983, at the University of Bristol, looked brilliantly at these waves and found that they appear to come out of nowhere and then disappear quite suddenly again.…”
Section: L=ngdmentioning
confidence: 98%
“…The study of rogue waves in metamaterials is currently at an early stage 6 , however. Only a few recent numerical studies, based on a transmission line model (with NLSE reduction) or a cubic-quintic NLSE can be found.…”
Section: Optical Rogue Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews dealing with wave propagation in hyperbolic metamaterials and applications are given in Refs. [58][59][60]. In this work we investigate if HMM could provide a good platform for realizing the strong coupling regime using the collective excitations of emitters.…”
Section: Introductionmentioning
confidence: 99%
“…For p-polarization in vacuum movement for E-PP requires the solution of DE and the calculation of the integral from z over infinite cross section, which is a more complicated procedure. In addition, the formula(20) is written for an infinite sample, and then it is possible to substitute any of the two values  x k of(6). For the final sample, two waves in the transverse direction should be taken into account and their determined amplitudes (see below), which further complicates the task.…”
mentioning
confidence: 99%